The effectiveness of the application of comprehensive measures to combat erosion using irrigation in a market economy in Azerbaijan (on the example of the Kur-Araks plain): The effectiveness of the application of comprehensive measures to combat erosion - Aliyev, Z. H. (B.R. Nahata Smriti Sansthan Agricultural Extension Journal (AEXTJ), 2021)
Studies in the article have shown that productivity increases with improved structure. This is explained by the fact that in soils with 0.25 mm diameter, water-resistant aggregates of 14%, grain yield is 22.2 cents/ha, while water-resistant aggregates are 8%. In soils, this figure decreased to 18.4 cents/ha (3.8 cents/ha). It is also known that alfalfa plays a key role in improving the water physical properties of the soil, as well as its agrochemical composition. The author’s research shows that the amount of water-resistant aggregates under the clover is much higher than in the cotton fields. This can be clearly seen from the following comparison. Thus, the amount of water-resistant aggregates in 0–10 cm of soil in the cotton field is 4.0–18.5; while 0.5 cm is 6.5–11.2 and 20–30 cm is 4.5–18.2, in clover crops, this indicator is 35.0; increased to 24.7 and 27.0. In addition, it revealed the accumulation of more organic and mineral substances under alfalfa cultivation. They proved this by the analysis of soil samples taken from the 1-year and 2-year plots. It was found that 1.66% humus and 0.112% total nitrogen were accumulated in the topsoil of the annual alfalfa field, while the amount of humus accumulated in the topsoil in the biennial clover field was 1.70% and the total nitrogen content was 0.150%. It should be noted that the development of irrigation erosion in irrigated arable lands depends on the fact that the surface of the area is covered with a large cover. This was clearly shown by the observations. It was found that both relatively weak (0.4 mm/min) and very (1.4 mm/min) heavy rains protect clover soil from further washing. Thus, 0.4 mm/min. In heavy rains, the depth of the furrow under alfalfa is 14.4 mm, 31 mm at 1.4 mm/min, 50.9 and 64.2 mm between rows of cotton, respectively, and 78.6 and 113 mm along the row 6 mm.